2016
DOI: 10.1007/s12603-016-0851-6
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve the oral health of people with dementia or cognitive impairment: A review of the literature

Abstract: There is a lack of high quality evidence to support the effectiveness of oral health interventions and implementation strategies for older people with dementia or cognitive impairment. More rigorous, large scale research is needed in this area. Recommendations are provided to improve the overall quality of evaluation in this area. Emphasis must be placed on developing evidence-based, achievable and sustainable oral health strategies if the needs of people with dementia and cognitive impairment are to be met in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…Knowledge, self‐efficacy and factors enabling desirable behaviour are often addressed, but the authors point out that memory training, clinical feedback and social norms ought to be studied. Focusing on people with dementia, both Siegel et al and Rozas et al pointed out a lack of knowledge regarding effective methods to improve oral health, so no recommendations could be made concerning specific interventions. Two systematic reviews by Hoben et al and a review by Albrecht et al stressed the low quality of the available evidence and the need of rigorous studies using relevant outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge, self‐efficacy and factors enabling desirable behaviour are often addressed, but the authors point out that memory training, clinical feedback and social norms ought to be studied. Focusing on people with dementia, both Siegel et al and Rozas et al pointed out a lack of knowledge regarding effective methods to improve oral health, so no recommendations could be made concerning specific interventions. Two systematic reviews by Hoben et al and a review by Albrecht et al stressed the low quality of the available evidence and the need of rigorous studies using relevant outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Further the systematic reviews concluded that training programmes can increase knowledge among care professionals and influence their attitudes on oral health 32,33,35 but no specific interventions aimed for changing the behaviour of nursing staff had positive outcomes. [36][37][38][39] Although knowledge was found in several areas, knowledge gaps were identified within majority of the investigated domains.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging them in adequate oral hygiene practices at an earlier stage of their cognitive impairment might make it possible for them to maintain these practices as their cognition declines. A recent literature review, specific to oral hygiene, found that effective interventions for activities of daily living included threat reduction techniques, such as gesturing or cueing, 12 which Jablonski and colleagues coined "treat reduction" techniques. 13 A literature review not specific to oral hygiene found prompting to be effective in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…This too however, should be interpreted with caution as there are many confounding factors which need to be identified before any definitive conclusion can be drawn about the effectiveness of the oral health training component for staff. There is a body of evidence which indicates that education and training of staff, while important, is not sufficient to improve oral health outcomes, such as decreasing dental caries and periodontal diseases 21. The environment in which public dental services are delivered in Australia is another major limiting factor on sustainable domiciliary models of dental care.…”
mentioning
confidence: 99%